Diffusion weighted MRI in evaluation of transplanted kidney: Preliminary clinical experience - El-Ghar, Mohamed Abou; Refaie, Huda; Hassan, Nabil; Kamal, Mohamed; Mohsen, Tarek; El-Diasty, Tarek (African Journal of Nephrology, 2009)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Purpose: To evaluate the diagnostic performance ofDiffusion Weighted (DW) magnetic resonance(MR) imaging in evaluation of transplantedkidneys. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Patients and methods: One hundred twelve patientswith transplanted kidney from live kidney donorswere evaluated with coronal T2w and DW MRI ofthe kidney. There was 86 males and 26 females andthe mean age was 26.911.5ys (range 10-55).Apparent diffusion coefficient (ADC) wascalculated and the kidneys studied for any areasdiffusion restriction. Our patients classified into 2groups: Group 1 included 81 patients with stablekidney function and normal serum creatinine andthe second group included 31 patients with alteredkidney function, it includes 18 patients with chronicnephropathies and 13 patients with acute cellularrejection. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: The mean ADC values for group 1 was2.70.26 x 10-3 mm2 /sec (range 1.93-3.6). In casesof chronic nephropathies, the mean ADC valueswas 2.30.22mm2/sec (range 2.05-2.77) while incases of acute cellular rejection it was1.80.2mm2/sec (range 1.7-2.2). When we use the2.4mm2/sec as a low cutoff ADC value fordiagnosis of normal kidney function, the sensitivity,specificity and overall accuracy for DWI MRI was80%, 96% and 93.5% respectively. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">When we used the ADC value of 2mm2/sec as acutoff value between acute cellular rejection andchronic nephropathies, the sensitivity, specificityand overall accuracy of DWI MRI was 90%, 98%and 90% respectively. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: In this relatively large study includingstable and abnormal function in transplantedkidneys, we can conclude that DW MRI isrelatively a new technique that allows diagnosis oftransplanted kidney with normal and alteredfunction.